2021
DOI: 10.1002/pol.20210603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cellulose nanocrystals on the vulcanization of natural rubber/cellulose nanocrystals nanocomposite and corresponding regulating strategies

Abstract: Vulcanization is a vital process in rubber processing, it endows rubber with valuable physical and mechanical properties, making rubber a widely used engineering material. In addition to vulcanization agent, reinforcing fillers play a non-ignorable influence on the vulcanization of rubber nanocomposites. Herein, the effects of cellulose nanocrystals (CNCs) on the vulcanization of natural rubber (NR)/CNCs nanocomposite was studied. It was found that even though the addition of CNCs can effectively improve the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For 25E composites, M H was slightly higher than that of the neat NR and 15E compounds, compared to the same level of CNC content. The higher epoxide level might improve rubber–CNC interaction that minimized the possible interaction between CNC and ZnO, the activator in vulcanization 34 . Moreover, it was found that the CNC amount did not influence the M H of rubber compounds because the amount of CNC might not be high enough to raise the M H of the rubber compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 25E composites, M H was slightly higher than that of the neat NR and 15E compounds, compared to the same level of CNC content. The higher epoxide level might improve rubber–CNC interaction that minimized the possible interaction between CNC and ZnO, the activator in vulcanization 34 . Moreover, it was found that the CNC amount did not influence the M H of rubber compounds because the amount of CNC might not be high enough to raise the M H of the rubber compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The higher epoxide level might improve rubber-CNC interaction that minimized the possible interaction between CNC and ZnO, the activator in vulcanization. 34 Moreover, it was found that the CNC amount did not influence the M H of rubber compounds because the amount of CNC might not be high enough to raise the M H of the rubber compounds. A similar incident was reported by Bhagavatheswaran et al who found that nitrile rubber (NBR) filled with 5 and 10 phr of eggshell or CaCO 3 gave a slightly lower maximum torque than that of the neat NBR.…”
Section: Cure Characteristics Of Rubber/cnc Compoundsmentioning
confidence: 99%
“…14 Although cellulose has many excellent advantages, the poor interfacial adhesion between cellulose and the polymer matrix, which makes it easily agglomerates in the polymer matrix and cannot exert its reinforcing effect and limits its application in the polymer matrix and is a major drawback in the use of natural fibers as reinforcement. [15][16][17] Therefore, cellulose needs to be modified before filling the polymer to improve the interfacial bonding between cellulose and the polymer matrix. Several studies have reported the application of cellulose as an effective filler for rubber composites in place of commonly used fillers such as carbon black (CB) and silica.…”
Section: Introductionmentioning
confidence: 99%